Legal Empowerment for SMEs Regarding Collective Marks: A Legal Analysis - Siti Nur Azizah,; Eny Sulistyowati,; Sulaksono,; Muh. Ali Masnun,; Syahid Ahmad Faisol, (Technium Social Sciences Journal, 2023)
This study aims to conduct a legal analysis regarding the empowerment of SMEs in obtaining protection for collective trademark rights. This article uses doctrinal research (normative juridical), using primary and secondary legal materials and non-doctrinal using primary data. The results of the research and discussion show that empowering MSMEs through collective brand protection needs to be considered from both normative and empirical aspects. From the normative aspect, there are still inconsistent arrangements and unclear norms. while at the empirical level the provision of collective brand protection for MSMe is relatively difficult to realize.